Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

Discovery and engineering of a formate dehydrogenase with enhanced bicarbonate reduction activity - Feng Lu; Runxin Liang; Yimiao Chen; Xiao Li; Ruolin Yang; Yuhong Huang; Wangtao Jiang; Yongtong Feng; Ping Gui; Xuefeng Wang; Fuqiang Ma (Bioresource Technology, 2026)

Activation-free hydrogen release and uptake in MgH2 enabled by flower-shaped NiMn bimetallic oxides - Yi Chen; Yunlong Zhang; Ruolin Li; Xiaojiang Hou (Chemical Engineering Journal, 2026)

Metabolomic insights into flavonoid migration and bioactivity enhancement in Apocynum venetum tea during hot-water brewing - Syeda Wajeeha Gillani; Kuo Xu; Ping Li; Xueli Lu; Bo Wang; Lu Wang; Juying Wang; Guosheng Wang; Ruolin Song; Tingting Ren; Chen Meng; Yiqiang Li; et al. (Food Chemistry, 2026)

Self-assembled carrier-free Cur@EGCG-Cu rescue inflammatory senescence and restore autophagy in tendinopathy - Yu Zhang; Qiqi Lou; Ran Yang; Xiang Li; Xiangkai Kong; Ruolin Cui; Ni Ni; Lilun Jin; Weiran Teng; Ping Gu (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Unlocking catalytic capacity of (S)-selective ω-transaminases toward aryl methyl ketones via pocket engineering and droplet screening - Ping Gui; Xiao Li; Wangtao Jiang; Ruolin Yang; Peiyao Chang; Xingwang Qie; Xinrui Wang; Xuefeng Wang; Jingjie Jiang; Liyan Wang; Xiaojie Guo; Hongbin Zou; et al. (Bioresource Technology, 2026)

Tailoring high-performance blend cementitious composites by co-recycling incineration fly ash, glass powder, and blast furnace slag - Yingying Xiong; Ruolin Zhao; Yan Xia; Liang Zhao; Bo Li; Atabaev F. Baxtiyarovich; Patryk Oleszczuk; Małgorzata Wiśniewska; Zengyi Ma; Lei Wang (Waste Disposal & Sustainable Energy, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Dissecting the genetic architecture of silique-related traits in rapeseed (Brassica napus L.) through genome-wide association studies and transcriptome analysis - Cuiping Zhang; Guangze Li; Ruolin Gong; Yunfei Zhang; Pan Lu; Chunyan Dai; Niannian Fan; Wu Yao; Xue Shi; Jungang Dong; Jihong Hu (Theoretical and Applied Genetics, 2026)

A mutation in CsBRP1, encoding a PHD-type domain-containing protein, causes semi-dwarfism in cucumber (Cucumis sativus L.) - Xiaoxu Han; Juan Yin; Xueying Jiao; Ruolin Hu; Yingjie Zhang; Fahang Chen; Biao Dong; Chunyan Cheng; Yuhui Wang; Chunhua Wang; Ji Li; Tao Wu; et al. (Theoretical and Applied Genetics, 2026)

Genome-wide association mapping of native QTLs for Fusarium head blight resistance in US winter wheat - Ruolin Bian; Yaoguang Li; Yanhong Dong; Xiaomao Lin; Guihua Bai (Theoretical and Applied Genetics, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Flammability limits and near-limit kinetic behaviors of multi-component syngas: A combined experimental and numerical study - Zhenmin Luo; Ruolin Hao; Bin Su; Lu Liu; Dinghan Li; Litao Liu; Shangyong Zhou; Tao Wang (Fuel, 2026)

Synergistic cytotoxicity of gymnodimine-A and okadaic acid in Caco-2 cells through coordinated disruption of calcium homeostasis and oxidative stress - Guixiang Wang; Jiangbing Qiu; Ruolin Wu; Aifeng Li; Ying Ji (Aquatic Toxicology, 2026)

Study of phenoxyethanol-citric acid biphasic pretreatment of sugarcane bagasse for enhanced enzymatic hydrolysis - Jili Liao; Ruize Wang; Xin Li; Ruolin Li; Danna Xie; Xiaoxue Zhao; Jing Wang; Caoxing Huang (Biomass and Bioenergy, 2026)

Combined effects of polystyrene nanoplastics and dinophysistoxin-1 (DTX1) on physiological performance of marine diatom Thalassiosira minima - Natnael Sisay Demo; Jiangbing Qiu; Guowang Yan; Ruolin Wu; Mohammad Sadiq Nikzad; Aifeng Li (Water Research, 2025)

Luminescence dating of core sediments from the southern coastal Bohai Sea, China, and its implications for transgression history during the Late Quaternary - Zhiqiang Xu; Yang Han; Bingpeng Yan; Mingbo Li; Ruolin Jiang; Ruonan Tian; Bohui Liu; Zihui Zhu; Weitao Yuan; Zhongping Lai (Frontiers in Marine Science, 2025)
Several marine strata have developed along the southern coastal Bohai Sea since the Late Quaternary, preserving abundant records of sedimentary evolution. This region is ideal for studying the sedimentary history of a river–sea interaction area. However, detailed sedimentological and chronological studies remain limited, mainly focusing on the estuaries of the Mihe River. In this study, 12 optically stimulated luminescence (OSL) samples were collected from the upper 20 m of a 101 m core to establish a chronological framework using quartz OSL dating. Grain-size analysis was also conducted to determine sedimentological characteristics. Results indicate that the quartz OSL ages range from >100 ka to 6.2 ± 0.4 ka, and we believe they were the minimum ages when equivalent dose (D e ) >ca. 250 Gy (sample DZK3-G07 and below) owing to OSL signal saturation. Our findings reveal a sedimentary hiatus between >100 ka and 19.8 ka. Holocene sediments are found above a depth of 8.4 m with an onset age of approximately 10.5 ka. A lacustrine layer (8.4–9.6 m) in core DZK3 was dated to 19.8–10.5 ka, which is much older than that of the limnetic and lagoon layers in other cores in this area. Based on sedimentary facies and dating results, no transgressive sediments were observed during marine isotope stage (MIS) 3, and T2 (Xianxian transgression) in the southern coastal Bohai Sea only occurred in MIS 5e. This sedimentary sequence pattern is consistent with global sea-level changes.

Designing super-compatibility all-solid-waste binders for stabilization/solidification of Cr-contaminated soil - Ruolin Zhao; Yan Xia; Lei Ren; Huanyu Li; Binglin Guo; Liang Chen; Lei Wang (Journal of Hazardous Materials, 2025)

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Effects of okadaic acid on Pyropia yezoensis: Evidence from growth, photosynthesis, oxidative stress and transcriptome analysis - Ruolin Wu; Jiangbing Qiu; Xianghai Tang; Aifeng Li; Yongmeng Yang; Xinyu Zhu; Xianyao Zheng; Wenke Yang; Guangyao Wu; Guixiang Wang (Journal of Hazardous Materials, 2025)

Boosting photocatalytic degradation of antibiotics: The role of alcohol solvent on the morphology and bandgap structure of FeWO4 used for peroxymonosulfate activation - Shengyu Jing; Han Li; Huagen Liang; Ruolin Cheng; Angeliki Brouzgou; Panagiotis Tsiakaras (Chemical Engineering Journal, 2025)

Investigating the mechanisms of flucarbazone-sodium resistance in Bromus japonicus Thunb - Yuning Lan; Xinhui Xue; Hailan Cui; Ruolin Wang; Ying Sun; Hongjuan Huang; Shouhui Wei; Xiangju Li; Zhaofeng Huang (Plant and Soil, 2025)

Ecological diversity and metabolic strategies of widespread Marinisomatota in global oceans - Shizheng Xiang; Jianyang Li; Zhen Chen; Ruolin Cheng; Liping Wang; Libo Yu; Guangshan Wei; Xiangyu Guan; Brandon R. Briggs; Gary King; Hongchen Jiang; Zongze Shao (Marine Life Science & Technology, 2025)

Precipitation recycling impacts on runoff in arid regions of China and Mongolia: a machine learning approach - Ruolin Li; Qi Feng; Yang Cui (Hydrological Sciences Journal, 2025)

Investigating the cooling effect of urban lakes from the perspective of their characteristics and surrounding landscapes: A case study of 82 urban lakes in China - Ruolin Huang; Hao Hou; Jiahui Li; Ronald C. Estoque; Yuji Murayama; Li Chen; Xinmin Zhang; Tangao Hu (Science of The Total Environment, 2025)

Lower toxicity of HFPO-DA compared to its predecessor PFOA to the earthworm Eisenia fetida: Evidence from oxidative stress and transcriptomic analysis - Ruolin Wu; Xiaole Wang; Jingwen Zhang; Chengbo Lu; Bing Li; Zhongkun Du; Jun Wang; Jinhua Wang; Yue Yang; Lusheng Zhu (Journal of Hazardous Materials, 2025)

Fluoroquinolone antibiotics trigger selective oxidation in the trace-Cu(II)/peroxydisulfate system: The synergistic effect of dual reactive sites in chemical structure - Jiahang Liu; Xiaoyang Li; Ruolin Lv; Yingying Chu; Mengying Qian; Weiming Zhang (Journal of Hazardous Materials, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

A rapid method for the assessment of crown rot severity caused by Fusarium pseudograminearum in wheat seedlings - Qiaoyun Li; Zhenfeng Guo; Ruolin Zhu; Zhao Yin; Xiaopeng Hao; Jianwei Tang; Chunhao Dong; Yuhao Yuan; Zhenpu Huang; Jishan Niu; Guihong Yin (European Journal of Plant Pathology, 2025)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Dracocephalum Moldavica L.-derived carbon dots for effective periodontitis treatment via reprogramming energy metabolism in macrophages - Bo Zhang; Ruolin Ding; Xi He; Yifei Li; Zhongshan He; Jie Fang; Mengran Guo; Xinchun Wang; Zhihe Zhao; Xiangrong Song (Chemical Engineering Journal, 2024)

Functional analysis of a rice 12-oxo-phytodienoic acid reductase gene (OsOPR1) involved in Cd stress tolerance - Longying Wu; Ruolin Wang; Mingyu Li; Zhiye Du; Yufan Jin; Yang Shi; Wenjun Jiang; Ji Chen; Yuan Jiao; Binhua Hu; Jin Huang (Molecular Biology Reports, 2024)

Occurrence and migration patterns of microplastics in different tidal zones of tourist beaches: A case study in the Bohai Bay, North China - Yutao Zuo; Yawen Ge; Ruolin Wang; Wanqiang Xu; Changhong Liu; Zixiao Guo; Shuo Wang; Huiyuan Jia; Yuecong Li (Journal of Environmental Management, 2024)

Multi-scale matching and simulating flows of ecosystem service supply and demand in the Wuhan metropolitan area, China - Ying Chen; Yina Lu; Ruolin Meng; Suran Li; Linzi Zheng; Min Song (Journal of Cleaner Production, 2024)

Environmentally persistent free radicals on photoaging microplastics shortens longevity via inducing oxidative stress in Caenorhabditis elegans - Hui Li; Yongqi Jiang; Yulun Gu; Chao Chen; Jun Yu; Chen Wang; Chongli Shi; Ruolin Pan; Haibo Chen (Chemosphere, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Preparation of casein hydrolysate by two-step enzymatic hydrolysis and its immunomodulatory activities in vitro and in vivo - Yutong Jiang; Siyi Li; Ruolin Yuan; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Machine learning: An accelerator for the exploration and application of advanced metal-organic frameworks - Ruolin Du; Ruiqi Xin; Han Wang; Wenkai Zhu; Rui Li; Wei Liu (Chemical Engineering Journal, 2024)

Life cycle assessment of bioproducts from bamboo residues with biphasic phenoxyethanol-acid based biorefinery technology - Caoxing Huang; Ruolin Li; Yayue Zheng; Kai Lan (Chemical Engineering Journal, 2024)

Characterization of a new greenbug resistance gene Gb9 in a synthetic hexaploid wheat - Xiangyang Xu; Genqiao Li; Guihua Bai; Ruolin Bian; Amy Bernardo; Tezera W. Wolabu; Brett F. Carver; Yanqi Wu; Norman Elliott (Theoretical and Applied Genetics, 2024)

Provenance of surface dune sands in the Gurbantunggut Desert, northwestern China: Qualitative and quantitative assessment using geochemical fingerprinting - Baofeng Li; Qi Feng; Zaijun Li; Fei Wang; Chongwen Luo; Ruolin Li; Han Hu (Geomorphology, 2024)

Influence of elevated temperature on the species and mobility of chromium in ferrous sulfate-amended contaminated soil - Ruolin Zhao; Xinqing Zhang; Yiwen Zhou; Jining Li; Binglin Guo; Keishi Oyama; Chiharu Tokoro (Journal of Environmental Management, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Oxidation of emerging contaminants by S(IV) activated ferrate: Identification of reactive species - Yingying Chu; Mujian Xu; Xiaoyang Li; Junhe Lu; Zhichao Yang; Ruolin Lv; Jiahang Liu; Lu Lv; Weiming Zhang (Water Research, 2024)

TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Jiali Weng; Qi Liu; Chenfei Li; Yi Feng; Qing Chang; Meiqin Xie; Xiaohui Wang; Mengnan Li; Hai Zhang; Ruolin Mao; Na Zhang; Xiaohua Yang; et al. (Science of The Total Environment, 2024)

Responses of the intestinal microbiota to exposure of okadaic acid in marine medaka Oryzias melastigma - Yongmeng Yang; Aifeng Li; Jiangbing Qiu; Dongmei Gao; Chao Yin; Dongyue Li; Wenhui Yan; Hui Dang; Peiyao Li; Ruolin Wu; Lilin Han; Xiaoyun Wang (Journal of Hazardous Materials, 2024)

Effects of particle size on the pyrolysis of waste tires during molten salt thermal treatment - Ruolin Li; Yang Ren; Chengyang Cao; Chao He; Hongyun Hu; Xian Li; Hong Yao (Fuel, 2024)

Environmentally persistent free radicals on photoaged nanopolystyrene induce neurotoxicity by affecting dopamine, glutamate, serotonin and GABA in Caenorhabditis elegans - Hui Li; Yulun Gu; Yongqi Jiang; Ping Ding; Xiaoxia Chen; Chao Chen; Ruolin Pan; Chongli Shi; Susu Wang; Haibo Chen (Science of The Total Environment, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

The impact of water quality on the formation of halogenated benzoquinones and the adsorption efficiency by activated carbon - Yongjing Wang; Song Gao; Xinyu Yan; Songtao Wang; Ruolin Zhang; Yan Zhou; Lianhai Ren; Cheng Li (Journal of Environmental Sciences, 2024)

TRIM21 of Micropterus salmoides exerts antiviral roles against largemouth bass ulcer syndrome virus - Zichao Peng; Caiyun Zhang; Baojie Yin; Yange He; Wenxian Li; Jinchao Wang; Jiaxin Xiao; Kaisong Peng; Chuanhe Bao; Ruolin Zhu (Fish & Shellfish Immunology, 2023)

An autocatalytic Fe(III)/H2O2 Fenton-like process triggered by tetracycline: The overlooked effect of quinone intermediates - Jiahang Liu; Xiaoyang Li; Yingying Chu; Ling Yuan; Ruolin Lv; Weiming Zhang (Chemical Engineering Journal, 2023)

Conversion of agricultural waste to porous hydrochar for non-metallic activation of persulfate to phenol degradation via non-radical-dominated processes: Singlet oxygen and electron transfer - Jianhua Qu; Wanying Tong; Jun Zhang; Kaiyin Ye; Linsong Xiang; Ruolin Li; Di Wang; Zihe Chen; Qi Hu; Guangshan Zhang; Lei Wang; Ying Zhang (Journal of Cleaner Production, 2023)

Microbial colonization of microplastics in wastewater accelerates the aging process associated with oxidative stress and the insulin/IGF1 signaling pathway - Haibo Chen; Mengfan Chen; Yulun Gu; Yongqi Jiang; Ping Ding; Chen Wang; Ruolin Pan; Chongli Shi; Hui Li (Environmental Pollution, 2023)

Effect of MOF-derived carbon–nitrogen nanosheets co-doped with nickel and titanium dioxide nanoparticles on hydrogen storage performance of MgH2 - Zhiqiang Lan; Feifan Hong; Weitao Shi; Ruolin Zhao; Renhuan Li; Yi Fan; Haizhen Liu; Wenzheng Zhou; Hua Ning; Jin Guo (Chemical Engineering Journal, 2023)

The effect of TiO2NPs on cloransulam-methyl toxicity to earthworm (Eisenia fetida) - Ruolin Wu; Hunan Liu; Chengbo Lu; Kaixuan Hou; Xiaole Wang; Jun Wang; Zhongkun Du; Bing Li; Lusheng Zhu; Jinhua Wang (Chemosphere, 2023)

Chemical weathering evidence for East Asian Summer Monsoon rainfall variability in the upper reaches of the Yellow River since the Early Pleistocene - Baofeng Li; Qi Feng; Fei Wang; Zaijun Li; Xin Wang; Ruolin Li; Weiyu Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Novel carbon-coated zirconium oxide nanocomposites enable ultrahigh oxidant utilization efficiency for selective degradation of organic contaminants - Xiaoyang Li; Jiahang Liu; Ruolin Lv; Yingying Chu; Lu Lv; Junhe Lu; Weiming Zhang (Chemical Engineering Journal, 2023)

Amorphous zirconium oxide activates peroxymonosulfate for selective degradation of organic compounds: Performance, mechanisms and structure-activity relationship - Xiaoyang Li; Ruolin Lv; Weiming Zhang; Mingyang Li; Junhe Lu; Yi Ren; Yue Yin; Jiahang Liu (Water Research, 2023)

An R2R3-MYB FtMYB11 from Tartary buckwheat has contrasting effects on abiotic tolerance in Arabidopsis - Qian Chen; Lu Peng; Anhu Wang; Lingzhi Yu; Yu Liu; Xinrong Zhang; Ruolin Wang; Xiaoyi Li; Yi Yang; Xufeng Li; Jianmei Wang (Journal of Plant Physiology, 2023)

Leaching of heavy metal(loid)s from historical Pb–Zn mining tailing in abandoned tailing deposit: Up-flow column and batch tests - Yuan Yao; Lizhi Tong; Ruolin Zhao; Qianhui Wang; Jinli Qiu; Fenghe Wang; Jining Li; Yifan Yan; Yue He; Shuqin Li (Journal of Environmental Management, 2023)

Toxicity comparison of atrazine on Eisenia fetida in artificial soil and three natural soils - Xiaoying Li; Yue Yang; Ruolin Wu; Kaixuan Hou; Samuel C. Allen; Lusheng Zhu; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

PLAGL2 increases adriamycin resistance and EMT in breast cancer cells by activating the Wnt pathway - Yuxiao Li; Ruolin Liu; Xingzhao Han; Wei Xu; Yahui Liu (Genes & Genomics, 2023)

Variation in the attached community structure and function of artificial habitats during ecological succession: A case study of the artificial reef area in Bailong Pearl Bay, China - Ruolin Li; Yu Guo; Ankai Zhang; Shuo Zhang; Hui Zhang; Chuanxin Qin (Frontiers in Marine Science, 2022)
With the continuous development of ports, ship transportation, resource extraction and artificial habitat deployment, an increasing number of artificial structures have created new usable spaces for marine organisms, and the biological communities living on their surfaces have undergone ecological succession. However, related studies have ignored ecological functions, interspecific relationships, and stability in different successional stages. Based on traditional taxonomy, this study applied functional diversity, niche overlap and niche breadth indexes to compare the attached organisms on artificial reefs (ARs) with different construction times in Bailong Pearl Bay, Fangchenggang City, Guangxi Zhuang Autonomous Region, China. The change trends of richness, habitat resource supply, resource utilization degree and efficiency, and interspecific relationships during the succession process were analysed. The results indicated that richness increased with functional diversity. While the number of species increased, the attached organisms showed different functional characteristics, and the number of species with identical traits decreased. The attached community in the later stage of development had a higher degree of utilization of ecological space, more comprehensive and efficient utilization of effective resources, a stronger degree of complementarity of organismal niches, and weaker interspecific competition. In the early stage of the developmental process, the attached community was affected by more environmental factors and had very significant correlations with those factors. The combination of the niche overlap index and the niche breadth index indicated that the resource supply supporting the survival and development of the attached organisms on the ARs with earlier construction times may be greater. The decrease in the number of biomarkers, the similarity of biomarkers belonging to the same family, and the similarity of dominance alternation all indicated that during the process of long-term development and community succession, the organisms attached to the various parts of the ARs tended to become more similar.

Identification and characterization of the novel leaf rust resistance gene Lr81 in wheat - Xiangyang Xu; James Kolmer; Genqiao Li; Chengcheng Tan; Brett F. Carver; Ruolin Bian; Amy Bernardo; Guihua Bai (Theoretical and Applied Genetics, 2022)

Early warning model for death of sepsis via length insensitive temporal convolutional network - Minghui Gong; Jingming Liu; Chunping Li; Wei Guo; Ruolin Wang; Zheng Chen (Medical & Biological Engineering & Computing, 2022)

New Insight Into the Mechanism of Ecological Effects of Artificial Habitats: Elucidating the Relationship Between Protists Associated With Artificial Reefs and Adjacent Seawater - Ruolin Li; Yu Guo; Chuanxin Qin; Shuo Zhang; Dongping Ji; Hui Zhang; Jing Wang; Naiqian Zhao (Frontiers in Marine Science, 2022)
Artificial habitat deployment can restore natural habitats or supplement existing natural habitats. The effect of resource proliferation and protection is obvious. However, few reports have addressed the biological community association between artificial habitats and adjacent environments. Here, Illumina sequencing of 18S rDNA was performed, and the diversity, community structure, and co-occurrence networks of protists in different layers of artificial reefs (ARs) and adjacent seawater (WAR) were described to verify that constructing ARs in Bailong Pearl Bay improves local spatial heterogeneity and functional diversity. In terms of the degree of species interaction, the protist communities were ranked as follows: surface and bottom of WAR > ARs and WAR > different layers of ARs. The α-diversity of protists associated with ARs and WAR decreased with an increase in depth. Protist diversity was greater in WAR than in ARs. β-Diversity analysis revealed significant differences in protist community structure between WAR and ARs ( P < 0.05), and the upper layers of ARs and the middle or bottom layers of ARs differed. The key topological features of protist networks showed more positive interspecific interactions in the AR-associated protist community, a higher degree of niche differentiation, and higher complexity and stability. The keystone protists in the bottom seawater layer displayed community functions that were biased toward initial fixation in the ocean carbon cycle. The AR-associated protist community tended to participate in carbon transfer in the food chain and decomposition and utilization of dissolved organic matter (DOM). This study revealed significant differences in protist community structure between ARs and the adjacent environment, and the ecological functions of the key phyla were found to be related. In conclusion, protist communities in WAR may provide food sources for AR-associated heterotrophic protists. A variety of key phyla associated with ARs have biological roles in the carbon pump via their ecological characteristics.

Induced sputum metabolomic profiles and oxidative stress are associated with chronic obstructive pulmonary disease (COPD) severity: potential use for predictive, preventive, and personalized medicine - Tao Zhu; Shanqun Li; Jiajia Wang; Chunfang Liu; Lei Gao; Yuzhen Zeng; Ruolin Mao; Bo Cui; Hong Ji; Zhihong Chen (EPMA Journal, 2020)
Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease, and metabolomics plays a hub role in predictive, preventive, and personalized medicine (PPPM) related to COPD. This study thus aimed to reveal the role of induced sputum metabolomics in predicting COPD severity. In this pilot study, a total of 20 COPD patients were included. The induced sputum metabolites were assayed using a liquid chromatography-mass spectrometry (LC-MS/MS) system. Five oxidative stress products (myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione (GSH), neutrophil elastase (NE), and 8-iso-PGF2α) in induced sputum were measured by ELISA, and the metabolomic profiles were distinguished by principal component analysis (PCA) and orthogonal projections to latent structures discriminant analysis (OPLS-DA). The Kyoto Encyclopedia of Genes and Genomes (KEGG) was used for pathway enrichment analysis, and a significant difference in induced sputum metabolomics was observed between moderate and severe COPD. The KEGG analysis revealed that the glycerophospholipid metabolism pathway was downregulated in severe COPD. Due to the critical role of glycerophospholipid metabolism in oxidative stress, significant negative correlations were discovered between glycerophospholipid metabolites and three oxidative stress products (SOD, MPO, and 8-iso-PGF2α). The diagnostic values of SOD, MPO, and 8-iso-PGF2α in induced sputum were found to exhibit high sensitivities and specificities in the prediction of COPD severity. Collectively, this study provides the first identification of the association between induced sputum metabolomic profiles and COPD severity, indicating the potential value of metabolomics in PPPM for COPD management. The study also reveals the correlation between glycerophospholipid metabolites and oxidative stress products and their value for predicting COPD severity.

Isotopic fingerprinting of dissolved iron sources in the deep western Pacific since the late Miocene - Ruolin Liu; Bai Guo; Maoyu Wang; Weiqiang Li; Tao Yang; Hongfei Ling; Tianyu Chen (Science China Earth Sciences, 2020)

Effect of enhancers on the phytoremediation of soils polluted by pyrene and Ni using Sudan grass (Sorghum sudanense (Piper) Stapf.) - Xiaoyan Liu; Siyuan Shen; Xinying Zhang; Xintong Chen; Ruolin Jin; Xinyi Li (Environmental Science and Pollution Research, 2020)

Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures - Shasha Shang; Gaofeng Zhu; Ruolin Li; Jie Xu; Juan Gu; Huiling Chen; Xiaowen Liu; Tuo Han (International Journal of Climatology, 2020)
As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere.

Precipitation recycling using a new evapotranspiration estimator for Asian-African arid regions - Ruolin Li; Chenghai Wang (Theoretical and Applied Climatology, 2020)

Dissection of genetic factors underlying grain size and fine mapping of QTgw.cau-7D in common wheat (Triticum aestivum L.) - Zhaoyan Chen; Xuejiao Cheng; Lingling Chai; Zhihui Wang; Ruolin Bian; Jiang Li; Aiju Zhao; Mingming Xin; Weilong Guo; Zhaorong Hu; Huiru Peng; Yingyin Yao; et al. (Theoretical and Applied Genetics, 2020)

Skeletal muscle proteome analysis provides insights on high altitude adaptation of yaks - Wenting Wen; Zheze Zhao; Ruolin Li; Jiuqiang Guan; Zhiwei Zhou; Xiaolin Luo; Surendranath P. Suman; Qun Sun (Molecular Biology Reports, 2019)

Anaerobic digestion of tobacco stalk: biomethane production performance and kinetic analysis - Lyu Li; Ruolin Wang; Zhenlai Jiang; Wanwu Li; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2019)

The biotechnological potential of anaerobic fungi on fiber degradation and methane production - Yanfen Cheng; Qicheng Shi; Ruolin Sun; Dong Liang; Yuanfei Li; Yuqi Li; Wei Jin; Weiyun Zhu (World Journal of Microbiology and Biotechnology, 2018)

Changes in precipitation recycling over arid regions in the Northern Hemisphere - Ruolin Li; Chenghai Wang; Di Wu (Theoretical and Applied Climatology, 2018)

Association between non-steroidal anti-inflammatory drug use and melanoma risk: a meta-analysis of 13 studies - Shan Li; Yanqiong Liu; Zhiyu Zeng; Qiliu Peng; Ruolin Li; Li Xie; Xue Qin; Jinmin Zhao (Cancer Causes & Control, 2013)